2000
DOI: 10.1086/317425
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Influenza Infections during Epidemics with Use of a Clinical Case Definition

Abstract: Combined pharyngeal and nasal swab specimens were collected from 100 subjects who presented with a flu-like illness (fever >37.8 degrees C plus 2 of 4 symptoms: cough, myalgia, sore throat, and headache) of <72 hours' duration at 3 different clinics in the province of Quebec, Canada, during the 1998-1999 flu season. The rate of laboratory-confirmed influenza infection was 72% according to cell culture findings and 79% according to the results of multiplex reverse-transcription polymerase chain reaction (RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
259
8
17

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(303 citation statements)
references
References 15 publications
19
259
8
17
Order By: Relevance
“…Similarly, our study showed that the QuickVue Influenza Test has a high diagnostic yield for the detection of influenza infection among hospitalised children during the influenza season. The observed performance of the QuickVue Influenza Test is similar to that from previous studies with reported sensitivities and specificities varying between 74 and 93% and between 76 and 98% respectively [19,[27][28][29]. The observed PPV (79%) indicates that the majority of patients with positive rapid test truly have influenza infection, while the even greater NPV ( 93%) indicates that influenza infection is unlikely if the test is negative.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similarly, our study showed that the QuickVue Influenza Test has a high diagnostic yield for the detection of influenza infection among hospitalised children during the influenza season. The observed performance of the QuickVue Influenza Test is similar to that from previous studies with reported sensitivities and specificities varying between 74 and 93% and between 76 and 98% respectively [19,[27][28][29]. The observed PPV (79%) indicates that the majority of patients with positive rapid test truly have influenza infection, while the even greater NPV ( 93%) indicates that influenza infection is unlikely if the test is negative.…”
Section: Discussionsupporting
confidence: 81%
“…Specifically, the detection of influenza infection presenting with both fever and cough was observed to have sensitivities ranging between 64 and 86%, specificities between 55 and 67%, and PPVs ranging between 48 and 87% [5,6,19,20]. This contrasts other studies which reported that no clinical signs or symptoms are specific for influenza virus infection [21,22].…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Influenza surveillance programmes use a clinical case‐definition of viral infection to collect data on seasonal fluctuations in the incidence of acute respiratory illness in the community. Case definitions provide a rapid, non‐invasive and inexpensive way to alert surveillance programmes of potential increases in the rate of circulating influenza 10 , 11 , 12 , 13 . At times of high influenza circulation symptom‐based case definitions have been reported to be 60–70% accurate.…”
Section: Introductionmentioning
confidence: 99%
“…At times of high influenza circulation symptom‐based case definitions have been reported to be 60–70% accurate. In the absence of an epidemic and in the elderly, the predictive value of symptoms to diagnose influenza drops to only 44% 12 . The accuracy of symptoms to diagnose other viral infections in elderly COPD patients already vaccinated against influenza is unknown 14 , 15 …”
Section: Introductionmentioning
confidence: 99%